2023
DOI: 10.1021/acs.langmuir.3c02570
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanoclusters as Multienzymes Mimic Activities of Oxidase and Ascorbic Acid Oxidase in the Presence of Imidazole

Sikta Chakraborty,
Sarita Kolay,
Subarna Maity
et al.

Abstract: Artificial nanoenzymes based on metal nanoclusters have received great attention for multienzyme activities nowadays. In this work, pepsin-capped copper NCs (Cu-Pep NCs) are used as oxidase, ascorbic acid oxidase (AAO), and peroxidase mimics, and their activities are enhanced by the introduction of imidazole. The oxidase activity increased almost 7.5-fold, while 5-fold and 2fold increases were observed for the peroxidase and AAO-like activity, respectively. The enhanced radical formation in the presence of imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Metal nanoclusters with atomic precision have attracted significant interest owing to their structural diversity and fascinating optical properties to find out various potential applications. Synthesis of atomically precise NCs, understanding of their electronic structure, and electron–phonon coupling are essential to designing metal clusters with their tailored optical properties. A few strategies have been used to synthesize highly luminescent metal clusters by tailoring several atoms and surface staple motifs. Some of the efficient methods, such as one-pot reduction, ligand exchange, inter-NC reaction, thermodynamic and kinetic control over the desired product, etc., have been employed to fabricate stable thiolated Ag NCs. The noncovalent interactions of ligands are crucial for the stability of the NCs. It is reported that primary ligands (thiolates) protect the metal core only, and the thiolate and phosphine can stabilize the NCs. Zheng et al have reported that the secondary PPh 3 ligand can shrink the Ag NC size and influence their luminescence property . Bakr et al have reported that the coligands of phosphines allow the NCs for high-quality crystal growth .…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoclusters with atomic precision have attracted significant interest owing to their structural diversity and fascinating optical properties to find out various potential applications. Synthesis of atomically precise NCs, understanding of their electronic structure, and electron–phonon coupling are essential to designing metal clusters with their tailored optical properties. A few strategies have been used to synthesize highly luminescent metal clusters by tailoring several atoms and surface staple motifs. Some of the efficient methods, such as one-pot reduction, ligand exchange, inter-NC reaction, thermodynamic and kinetic control over the desired product, etc., have been employed to fabricate stable thiolated Ag NCs. The noncovalent interactions of ligands are crucial for the stability of the NCs. It is reported that primary ligands (thiolates) protect the metal core only, and the thiolate and phosphine can stabilize the NCs. Zheng et al have reported that the secondary PPh 3 ligand can shrink the Ag NC size and influence their luminescence property . Bakr et al have reported that the coligands of phosphines allow the NCs for high-quality crystal growth .…”
Section: Introductionmentioning
confidence: 99%